ANALISIS KONTRIBUSI PAJAK DAERAH DAN RETRIBUSI DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PEMERINTAH KAB. NIAS TAHUN 2019-2021 - Yakini Buulolo; Buulolo, Nanny Artatina; Zai, Kurniawan Sarototonafo; Telaumbanua, Eliagus (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
In 2019 - 2021, the plan for local tax revenues and regional levies at the Nias Regency Government is not in accordance with the realization of revenues. The contribution of local tax revenues and regional levies is still low when compared to other items of legitimate local original revenue. This study aims to describe the contribution of local taxes in increasing the local revenue of the Nias Regency Government from 2019–2021 and describe the contribution of regional levies in increasing the original revenue of the Nias Regency Government from 2019–2021. The research method used is a quantitative descriptive method that uses secondary data and literature with data sources coming from the Nias Regency Regional Financial and Revenue Management Agency. In this study, the time period used was 2019-2021 with data analysis using overlay analysis techniques. The results showed that the contribution value was carried out with a matrix of regional tax revenue and regional levies based on analysis of financial statement data from 2019-2021. Within a period of 3 (three) years from 2019 - 2021, the value of regional tax contributions and regional levies including criteria is very lacking in contributing to local original revenue. Keywords: Contribution of Local Tax, Local Retribution, Local Revenue.